FEATURES OF THE FORMATION OF VALUABLE ATTITUDES TOWARDS NATURE IN PRESCHOOL CHILDREN UNDER THE CONDITIONS OF THE STATE OF WAR - Matsuk, Ludmila (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article analyzes the peculiarities of the formation of a valuable attitude to nature in preschool children in the conditions of martial law. The following methods were used to solve the above-mentioned problem: analysis of philosophical, psychological-pedagogical and methodical literature on the research problem; methods of pedagogical diagnostics (questionnaires of educators, diagnostic methods for studying the value attitude towards nature in children of older preschool age). Following the goal, the following tasks were solved: to reveal the peculiarities of the formation of the value attitude towards nature among preschool children in the conditions of martial law, to substantiate and reveal the content of the criteria for the value attitude of older preschool children towards nature We consider a valuable attitude to nature as a special type of subjective attitude to the values of nature, which manifests itself in the emotions of satisfaction – dissatisfaction, joy – sadness, admiration – contempt in the process of interaction with certain objects of nature. The process of nurturing a valuable attitude towards nature (as a component of the ecological culture of the individual) is complex and is associated with the formation of a number of structural components of the individual: 1) needs to be determined by the functions of the natural environment; 2) emotional readiness to realize the values of nature; 3) motives for interaction with nature based on awareness of the values of nature; 4) personal experience of a valuable attitude to nature. Among the criteria of a valuable attitude to nature, the following were identified: peculiarities of perception of nature; the nature of the emotional reaction to the beauty of nature; the nature of motives for attitude towards nature and its protection; the nature of the assessment of one's attitude and the attitude of others towards natural objects. These criteria are basic for determining the types of value attitude towards nature in older preschool children: positive-active value attitude, positive-passive value attitude, neutral value attitude, negative value attitude.